(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2021)
We have studied the electronic band structures and magnetic properties of the naked zigzag graphene nano ribbons lying symmetrically on the ribbon’s middle under an external tensile strain along the edge direction by using first principle calculations. We have found that the ground state of unstrained line defects zigzag graphene nanoribbon’s was antiferromagnetism in which the magnetic moment localized on the line defect was negligible. When an external tensile strain was applied along the edge direction, the energy band near the Fermi level is spin-split. The band splitting was enhanced with increasing the strain, leading to an increase of the local magnetic moments on the defect. Graphene nanoribbons with zigzag edges are characterized with special localized states, showing a ferromagnetic order in the same edge but antiferromagnetic order between two opposite edges. The ferromagenetic ordering has been found to exist in graphene materials with defect such as vacancies, topological defects, edges and hydrogen chemisorptions. When the defect position changes a transmission from an antiferromagnetism semiconductor to an antiferro magnetism half metal appears. The tensile strain along the zigzag direction of graphene with topological line defects. The antiferromagnetic coupling between the magnetic moments on the edges and the line defects leaded to a turnover of polarization direction on one edge of a critical value of the tensile strain, causing the line defect zigzag graphene nanoribbon to be ferromagnetic. The obtained results were found in good agreement with previous results.